Aplikasi Sadd Al-Dzarai' Dalam Pasal 12 C Undang-Undang No 20 Tahun 2001 Tentang Penghapusan Pidana Penerima Gratifikasi - Suaidi (UNIVERSITAS BONDOWOSO, 2021)
One form of corruption is gratification. This crime is an important element in the reward exchange system and mechanism. The article regulating gratification is Article 12 C of Law 20/2001. The article states that officials who receive gratuities then report them to the Corruption Eradication Commission (KPK), so that in a formal juridical manner, such gifts are not considered bribes and cannot be criminalized. This article is considered to provide wider space and freedom for criminals because it is considered a space of tolerance for those who have received gratuities so that the perpetrators can easily repeat their actions. Therefore it is important to understand these rules with the Dzariah Sadd approach. Based on the concept of Sadd Dzariah, punishment for the perpetrator of gratification is not necessary to reject mafsadat. Thus, this rule of elimination is not justified because it will give mafsadat that is greater than benefit. As a rule of fiqh, darul mafasid muqaddamun 'ala jalbil mashalih (refusing damage should take precedence over taking profit